La revolución quimioinformática: enseñándole química a los robots - Montero-Bastidas, José Raúl (2024)
This article describes recent advances in the automation of organic chemistry focused on medicinal chemistry. Different platforms have enabled the execution of hundreds and even thousands of reactions in parallel to accelerate the discovery of pharmaceuticals. On the other hand, artificial intelligence models are being applied in organic chemistry to design experiments with conditions that increase the probability of success. Together, these advances promise to revolutionize organic synthesis and the fields of industry that depend on it.